Συνδυασμένη Χρήση Γεωπληροφορικής και Διαστημικών Τεχνολογιών για τον Εντοπισμό Υπεδάφιων Στρατιωτικών Εγκαταστάσεων στην Περιοχή της Κύπρου - Μέλιλλος, Γιώργος (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2018)
The detection of underground and ground military underground structures using satellite imagery and remote sensing could make a significant contribution to defense and security science. The launch of the first multispectral and hyperspectral satellites as well as high-resolution satellites confirms that the Remote Sensing industry is capable of delivering the most in these areas. This thesis aims to study underground military structures over vegetated areas using both ground and satellite remote sensing data. For the purposes of this research, several ground measurements have been carried out in military controlled areas, which are not accessible, throughout the phenological cycle of plant growth. The research was based on several reflectance’s measurements using ground spectroradiometers, using a SVC-HR1024 field spectroradiometer. Field spectroradiometric measurements were collected and analyzed to identify underground military structures using the spectral profile of the vegetated surface over the underground target and the surrounding area for in situ observations. Also reflectance’s measurements have been taken using small UAV which was equipment with hyperspectral and thermal sensors. Moreover, mean reflectances from different sensors such as Landsat 5, 7, 8, and Sentinel 2A were used using RSR filters. Multispectral vegetation indices were calculated to study variations in vegetation indices over vegetation areas in presence or absence of military underground structures. This thesis has contributed to the development of typical spectral signature, definition of a specific spectrum, evaluation of the application of vegetation indicators and finally the use of Sentinel 2A open satellite data for the detection of military underground structures. This thesis contributes significantly to the identification of variations in vegetation by the development of a new vegetation index while at the same time being able to determine the time limits in which these variations are maximized. Moreover, this thesis introduces for the first time in Cyprus the use of remote sensing in security and defense issues. Similar studies have been made in archaeology; however, the issue of detecting military underground structures remains a difficult issue to tackle due the inherent characteristics of such structures. The dissertation ends with the development of a proposed methodology for the use of satellite remote sensing for systematic monitoring of military subterranean constructions. This methodology can be used to provide useful data to the National Guard and to the Ministry of Defense of Cyprus for security purposes. Finally, this thesis cannot be published due to security and confidentiality reasons.
Keywords: Εδάφια; Υπεδάφια; Στρατιωτικές εγκαταστάσεις; Δορυφορικά τηλεπισκοπικά δεδομένα; Underground; Ground; Military underground structures; Spectroradiometers